1989
DOI: 10.1002/nbm.1940020509
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR study of cerebral development in the rat

Abstract: 1H NMR spectroscopy of brain extracts was used to investigate the metabolic changes that take place during development of the neonatal rat brain. Data were obtained over the range 1-21 days. The concentration of N-acetylaspartate rose by a factor of 9 during this period, the most rapid rise occurring after day 9. The total creatine concentration rose from days 1-21, with a large increase between days 1 and 5. Taurine concentration rose until day 5, then fell from days 5-21. The concentration of choline-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
32
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 19 publications
11
32
0
Order By: Relevance
“…It is a postulated source of acetate for lipid and myelin synthesis of oligodendrocytes (Satrustegui et al, 2007). As the immature rat brain develops, rapid increases in NAA are detected during the time of peak myelination (D'Adamo and Yatsu, 1966;Bates et al, 1989;Burri et al, 1990). Using purified rat brain mitochondria (Patel and Clark, 1979), the synthesis and transport of NAA out of mitochondria increased with brain development in concert with myelination.…”
Section: Discussionmentioning
confidence: 99%
“…It is a postulated source of acetate for lipid and myelin synthesis of oligodendrocytes (Satrustegui et al, 2007). As the immature rat brain develops, rapid increases in NAA are detected during the time of peak myelination (D'Adamo and Yatsu, 1966;Bates et al, 1989;Burri et al, 1990). Using purified rat brain mitochondria (Patel and Clark, 1979), the synthesis and transport of NAA out of mitochondria increased with brain development in concert with myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Urenjak et al (1993) have found that the qualitative and quantitative differences between 'H-NMR spectra obtained from different purified populations of neural cells appears to be strongly correlated with the lineage of the cell type examined. In this respect, the higher levels of NAA found in less-differentiated PNETs and Miyake and Kakimoto (1981) and Bates et al (1989), the relative contribution of the neuronal and 0-2A lineages to this rise is unclear. Therefore, it is not possible to say whether the NAA levels observed in PNET cell lines are typical of dividing neuronal progenitors of the cerebellum.…”
Section: Observations)mentioning
confidence: 99%
“…In vivo proton NMR spectroscopy methods have been used recently to investigate cerebral metabolism in human subjects, both in healthy adults (Frahm et al, 1990), and in patients presenting with focal lesions (Gill et al, 1990;Wolinsky et al, 1990) and diffuse disorders (Menon et al, 1990a, b). Metabolic processes have also been studied in a wide variety of animal models of the disease (Gadian et al, 1986;Bates et al, 1989b;Prichard & Shulman, 1986) and perfused organs (Cohen, 1983;Hollis, 1982), and in simpler systems such as isolated cell suspensions (Hollis, 1982;Navon et al, 1983), tissue extracts (Bates et al, 1989a;Gill et al, 1990) and body fluids (Bell et aL, 1989).…”
Section: Introductionmentioning
confidence: 99%